2008
DOI: 10.1111/j.1524-4741.2008.00649.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cavity Shaving on Reoperation Rate Following Breast-Conserving Surgery

Abstract: Breast-conserving surgery (BCS) without adequate margin clearance carries a high risk of local recurrence. We introduced cavity shaving at primary surgery 31 months ago, to assess tumor margin involvement. The aim of this study was to determine how cavity shaving affects the re-excision rate. We compared a group of 394 patients who underwent BCS with cavity shaving of macroscopically clear margins at primary operation, from March 2003 to September 2005 with a group of 392 patients who underwent BCS only from J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 16 publications
2
33
0
1
Order By: Relevance
“…Cao et al, found that 59% of103 patients who had positive margins on their initial specimen had negative margins after cavity shaving. 18,19 Tengher-Barna et al Similarly, found that 42% of 47 patients who had positive marginson their initial specimen had negative margins with cavity shaving. Jacobson et al 20,21 found that routine cavity shaving eliminated the need for a second surgery for margin clearance in 49% of 125 patients.…”
Section: Demographic and Clinical Patients' Data (Table)mentioning
confidence: 99%
“…Cao et al, found that 59% of103 patients who had positive margins on their initial specimen had negative margins after cavity shaving. 18,19 Tengher-Barna et al Similarly, found that 42% of 47 patients who had positive marginson their initial specimen had negative margins with cavity shaving. Jacobson et al 20,21 found that routine cavity shaving eliminated the need for a second surgery for margin clearance in 49% of 125 patients.…”
Section: Demographic and Clinical Patients' Data (Table)mentioning
confidence: 99%
“…The aim of BCS is to completely excise the tumour with negative margins and maintain satisfactory and acceptable cosmetic outcome. The importance of margin status of breast conserving surgery for breast cancer is well documented [3][4][5][6][7][8]. Although the overall survival rates for breast conversing surgery is equivalent to total mastectomy, margin status is an important determinant of local recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Although the overall survival rates for breast conversing surgery is equivalent to total mastectomy, margin status is an important determinant of local recurrence. It has been reported that approximately 20-40% of patients have positive margins after breast conserving surgery and require re-excision for clear margins [3,[6][7][8]. Negative margin does not mean a complete absence of residual unresected tumour in the treated breast, but it results in decreased tumour burden low enough to be treated with radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations